PENENTUAN PATAHAN DAN TOPOGRAFI MOHO PADA DATA NOAA-FA BERBASIS FFT - Bagus Jaya Santosa, Sungkono (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2010)
Regional Gravity NOAA-FA data analysis using several gradient methods has been conducted to determine the fracture and direction fault based on FFT. Fault can be qualitatively identified from a regional anomaly data, gradient Theta and Normalized Standard Deviation (NSD) is trending north-south. Dominant fracture orientation parallel to the fault is only detectable by gradient Theta and NSD, but more obviously displayed on the gradient NSD. Furthermore, regional anomaly of Gravity data inverted to generate Moho topography. This inversion using FFT based algorithm (Parker, 1972). The inversion result of Moho depths between 30-39 km. In the Moho topography, there is contrast depth difference, namely the Latitude -35 to -25 and Longitude -70 to -65, which is suspected as a fracture.Keyword: Gravity, FFT, Inversion, Fault, Fracture, Moho